Overcoming Speaking Anxiety Among Eight-Semester English Education Students at Universitas PGRI Yogyakarta - Yulianus Mekei; Andi Dian Rahmawan (Universitas PGRI Yogyakarta, 2025)
This study aims to determine the levels of students' speaking anxiety, identify the factors causing anxiety and find solutions to reduce it. This study is conducted due to students’ ignorance of anxiety and how to overcome it. The researcher used a mixed method to explore and explain students' problems on the speaking anxiety data. This research involved 21 students from the eight semesters of the English Education Department, PGRI Yogyakarta University. In collecting the data, the researcher used an FLCAS questionnaire by Horwitz (2019) and an interview. The questionnaire results determined student anxiety category into five categories from both low and high anxiety categories. After that, 10 students from the low anxiety and the high anxiety category were selected to be interviewed to find causes and solutions to deal with anxiety. The result of this study revealed 4 students were at very low anxiety levels, 3 students were included in the moderately low anxiety, 5 students were at moderate anxiety, 2 students were included in moderately high anxiety and, 7 students were at high anxiety levels. Furthermore, after identifying the interview result, the researcher found six factors causing students anxiety: students' poor English skills, the fear of misinterpretation, low self-esteem, fear of making mistakes then being criticized (fear of negative evaluation), lack of preparation, and excessive worry about tests.